Examining the employees and sectors of the economy according to the digital competence in the EU memeber states - Csordás, Adrián (International Journal of Engineering and Management Sciences, 2020)
In this study, the challenges of digital development and its sectoral effects were examined between 2015 and 2017 in the EU Member States, based on data of OECD, Eurostat, and the World Bank. The connection between the countries' digital development and sector dominance was analyzed. I found - in line with international research - that in countries that belong to the developed group, the high value-added service sector is dominant. The statistics of developing countries’ supported the assumption, that industry is the engine of the economy. The analysis of the underdeveloped countries revealed that agriculture and industry are the most important sectors compared to other countries. Measuring the demand of developed countries for ICT professionals, I examined the relationship of individuals with different digital competencies to one kind of self-education. In line with international research, my database showed that digitally unskilled people are the least likely to take advantage of online courses. As a continuation of the research, it would be worthwhile to carry out this study in other economic areas as well. Especially in areas where salaries for high-digital occupations do not differ significantly between countries in the region.